PENGARUH FAKTOR PSIKOLOGIS DAN WORD OF MOUTH TERHADAP KEPUTUSAN PENGGUNAAN BRT TRANS SEMARANG KORIDOR I - Wulandari, Kartika Ayu; Waluyo, Handoyo Djoko; Suryoko, Sri (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
The population density in Semarang causes various problems, such as traffic jam. BRT Trans Semarang is one of the government programs to overcome this problem. There are 4 BRT Trans Semarang’s corridor that operate now. Corridor I is the first corridor launched. The numbers of Corridor I passengers are increasing constantly. Nevertheless, the performance of BRT Trans Semarang is not optimal yet. This is showed by the articles in the newspaper about the BRT Trans Semarang’s services that need to be improved. Not Optimal services can lead to dissatisfaction of BRT Trans Semarang passengers. Furthermore, dissatisfaction can bring a bad reputation for BRT Trans Semarang. This research aims to see how the effect of Psychological Factors and Word Of Mouth in decision to the use of corridor I BRT Trans Semarang. Data collection technique used is interview and question, while data sample collecting technique used is purposive sampling with 100 sample. The data is analyzed through validity test, reliability test, crosstab, product moment correlation, coefficient of determination, simple linear regression, multiple linear regression, t-test and F-test. The data is analyzed quantitatively using the SPSS program version 20. The results showed that Psychological factors and Word Of Mouth have a significant influence in decision to the use of Corridor I BRT Trans Semarang partially. Psychological Factors and Word Of Mouth also have a significant influence in decision of the use of Corridor I BRT Trans Semarang simultaneously.